Hygiene and food safety practices among mothers as predictors of diarrhea risk in toddlers in Purwawinangun Village, West Java, Indonesia - Suparmi, Suparmi; Sasman, Muhammad Faris; Ratnawati, Ratnawati; Rustanti, Ninik (Frontiers in Public Health, 2025)
IntroductionWhile the factors contributing to diarrhea in children are well established, more literature on the influence of food hygiene practices on diarrhea in low-socioeconomic urban communities in Indonesia is still needed. This study investigated specific risk factors for toddlers’ diarrhea related to mothers’ personal hygiene and food safety practices.MethodsIt utilized a cross-sectional design with consecutive sampling, involving 36 mothers with toddlers in Purwawinangun Village, Cirebon, West Java, Indonesia. Hygiene and food safety practices, as well as diarrhea incidence, were assessed using a questionnaire.Results and discussionIn a bivariate analysis using Fisher’s Exact Test, personal hygiene practices [prevalence rate (PR) = 3.50; 95% confidence interval (CI) = 11.454–33.696] were significantly associated (p < 0.05) with an increased risk of diarrhea. Regarding mothers’ food safety practices, children of those with poor food safety were significantly associated (p < 0.05) with an increased risk of diarrhea compared to children of mothers who adhered to food safety guidelines (PR = 4.20; 95% CI = 12.127–89.524).ConclusionsThe risk of diarrhea in children can be mitigated by improving mothers’ hygiene behaviors and food safety practices. Mothers, especially those living in villages with limited water access, need ongoing education on the importance of food safety. To promote this practice, the local government can implement health initiatives to prevent diarrhea in children.